Teardowns: Learn How Electronics Work by Taking Them Apart - Bergerron Bryan (Mc Graw Hill, 2010)
Bryan Bergeron is editor of Nuts & Volts Magazine and Servo Magazine, the author of several hundred articles, and two dozen books, and owner of several patents. He teaches in the Harvard-MIT Division of Health Sciences and Technology. Bryan's company, Archetype Technologies, Inc., develops intelligent systems in the military.